Fabrication and characterization of disposable wireless electronic endoscope. (16th December 2016) - Chang, Ho; Chen, Chih-Hao; Liu, Ming-Hsing; Chien, Li-Ke; Huang, Tung-Sun; Tu, Bo-Hsiang
Abstract: A wireless electronic endoscope that transmits signals by Wi-Fi is developed for use in single-hole endoscopic surgery and future application to natural orifice surgery. The innovative electronic endoscope developed in this study has a disposable design, completely preventing patents from taking risks of cross infection. The main components of the endoscope are a disposable component of the front tip and the hand-held part of the rear tip. The front tip consists of a lens, metallic tube, and electronic joint whereas the rear tip consists of a power switch, image converter, wireless transceiver chip, and antenna. Experimental applications of the wireless electronic endoscope show that after 3 hours and 30 minutes of normal use, the temperature of metallic tube at the front tip averages 45 °C. Regarding the measured luminance result, when the focal distance is 5 cm, luminance reaches 1410 lux. In an indoor environment, when the measured distance is 3 m and there is no disruptor, the Wi-Fi transmitted signal of the endoscope is at strength −51 dBm. If the disruptor is established between the sending and receiving ends, signal strength is −53 dBm. Increasing the measured distance to 8 m obtains a signal strength of −74 dBm. Test practical applications indicate that the wireless Wi-Fi electronic endoscope fully meets the needs of surgery room.